Integrated environmental management of solid medical waste in medical facilities in the Capital Secretariat of Sana’a as a case study - Tahish, Khaled Hussein Abduallah; Al-Arashiy, Abdulwaly Mohsen Mohsen; Maiyas, Mohamed Ahmed Hamoud (Journal of natural sciences, life and applied sciences, 2023)
The study aimed at identifying the management level at which medical solid waste is processed through collection, transport and treatment. The study followed the analytical and descriptive approach as a tool for collecting data. The study comprised 35 health facilities including hospitals, health centers, and clinics located within the field of study. The data were analyzed using the SPSS statistical program. Moreover, the researcher applied Kai box test, arithmetic mean, and standard deviations for data processing. One of the most important findings of the study was the lack of an adequate medical waste management system in all hospitals, health centers and clinics. Another finding noted to the lack of a clear understanding of the meaning and risks of classification of medical wastes in the sample study. In addition, there is no infrastructure for sorting out as well as processing the medical waste that is disposed of in an unsuitable random landfill. The General Department of Hygiene and Improvement uses transport vehicles that are unsuitable for medical waste. The clothing and equipment appropriate to the nature of the work are not provided to drivers and employees leading to the occurrence of countless diseases. Therefore, it is necessary to pay attention and take all measures to detect and classify these wastes in order to reduce the risk and costs resulting from their improper management.